Accelerated forgetting and verbal memory consolidation process in idiopathic nondement Parkinson's disease - Hanoğlu, Lütfü; Ercan, Fatma Betül; Mantar, Nagihan; Yılmaz, Nesrin Helvacı; Sitrava, Sevilay; Özer, Feriha F.; Yuluğ, Burak (Elsevier, 2019)
Objective: Episodic memory impairment and underlying pathophysiology in Parkinson's Disease (PD) is poorly investigated. Formerly, it was thought to be a secondary effect of impairment in fronto-striatal circuit. However, recent studies hypothesized that there is a dual progression of PD and memory loss is possibly related to posterior cortex rather than frontal. To understand the impairment, underlying mechanisms should be investigated. Although consolidation is one of these mechanisms consolidation phase of episodic memory in PD was not investigated yet. Recently accelerated long term forgetting (ALF) phenomenon is emphasized in consolidation researches. Method: Here it is evaluated the presence of accelerated long-term forgetting in nondemented PD as a consequence of a deficit in consolidation process. 32 patients and 33 controls participated in the study. Turkish Verbal Memory Process Test (VMPT) was applied to both groups. Delayed recall (DR) scores collected after 30 min, one week and six weeks. Forgetting rates were calculated based on these scores. Results: There was significant difference in DR scores of patients compared to controls in the 30th minute and sixth week. Forgetting rate between 30th minute-1st week did not differ but 1st-6th week was found statistically significant across groups. Conclusions: To the best of our knowledge, this is the first study investigating verbal memory consolidation in PD. Results suggested that impairment is possibly related to the late phase of consolidation of verbal memory in neocortex.
Keywords: Parkinson's Disease; Consolidation; Accelerated Long-Term Forgetting; Verbal Memory